2016
DOI: 10.5301/tj.5000569
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Significance of Cofilin 1 Overexpression in Human Bladder Cancer

Abstract: Our study indicates that Cofilin 1 holds an important position in the development and progression of human bladder cancer, and this gene might become a novel target in the diagnosis and treatment of human bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
(19 reference statements)
4
10
0
Order By: Relevance
“…In this study, we found that Cofilin 1 expression was higher in bladder cancer tissues than in paracancerous tissues, which is consistent with previous results [ 32 ]. We also examined the effects of Cofilin 1 in the T24 and RT4 bladder cancer cell lines.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we found that Cofilin 1 expression was higher in bladder cancer tissues than in paracancerous tissues, which is consistent with previous results [ 32 ]. We also examined the effects of Cofilin 1 in the T24 and RT4 bladder cancer cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…Cofilin 1 also promoted bladder cancer growth in mouse xenograft experiments. Together, these results and previous studies suggest that Cofilin 1 may be a therapeutic target for bladder cancer [ 8 , 32 ]. ChIP and luciferase assays demonstrated that the transcription factor TCF7L2 bound to the promoter region of Cofilin 1 to regulate its expression.…”
Section: Discussionsupporting
confidence: 82%
“…Cofilin overexpression has been seen in lung cancer cells undergoing EMT [ 48 ] and in association with increased tumor cell invasion or metastasis [ 34 , 49 51 ]. Collazo and coworkers reported augmented levels of active cofilin in human prostate cancer and in experimental prostate tumors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a prostate cancer patient cohort, cofilin levels were increased and they were significantly higher in metastases than in primary tumors [ 33 ]. Cofilin level was also increased in bladder cancer [ 34 ], and in ovarian [ 35 ] and pancreatic cancer [ 36 ] overexpression of cofilin was associated with poor prognosis. In non-small-cell lung cancer (NSCLC) high cofilin level correlated with poor outcome and cisplatin treatment resistance [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of ARPC4 expression also led to the attenuation of proliferation, migration and invasion in these cells. 28 Wang et al 29 showed that both miR-182-5p and TCF7L2 30 were involved in the proliferation, migration, and invasion of bladder cancer cell through cofilin-1. Together these findings support a role for ARPC4, not only in the growth of bladder cancer but also in the tumor invasion and metastasis.…”
mentioning
confidence: 99%